Modeling lightweight cemented backfill considering progressive breakage. (September 2020) - Yu, Chengjun; Deng, An; Nguyen, Giang
Abstract: An analytical model for lightweight cemented backfill is presented. The model integrates elasto-brittle and elasto-plastic bodies, replicating responses of low-density materials and cementation that are present in backfills. The model uses a semi-implicit algorithm to iterate stress-strain solutions, and the universal shear contraction. The model was validated on a lightweight cemented backfill containing expanded polystyrene beads.